Grice’s Cooperative Principle in Talk Active 2 Textbook Dialogues - Elvaretha Lintang Novita; Christianti Tri Hapsari (Universitas Pahlawan Tuanku Tambusai, 2026)
Pragmatic competence is essential in EFL learning because students need to understand how meaning is used appropriately in context. Although many studies have examined pragmatics in English textbooks, limited research has investigated the representation of Grice’s maxims in Indonesian EFL textbooks, particularly Talk Active 2. This study aims to examine how Grice’s Cooperative Principle is represented in the dialogues of Talk Active 2 and to identify cases of maxim observance and non-observance. A descriptive qualitative design with content analysis was used. The data consisted of all 18 dialogues found in the textbook, which were analyzed based on the maxims of Quantity, Quality, Relation, and Manner. The findings show that most dialogues observe the maxims, while limited cases of non-observance appear as flouting and opting out. The study concludes that Talk Active 2 mainly presents cooperative and pedagogically simplified communication for EFL learners.